Effect of Fuel Cetane Number on Multi-Cylinders Direct Injection Diesel Engine Performance and Exhaust Emissions - Ahmed, Sabah Tarik; Chaichan, Miqdam Tariq (Al-Khwarizmi Engineering Journal, 2012)
Due to the energy crisis and the stringent environmental regulations, diesel engines are offering good hope for automotive vehicles. However, a lot of work is needed to reduce the diesel exhaust emissions and give the way for full utilization of the diesel fuel’s excellent characteristics.A kind of cetane number improver has been proposed and tested to be used with diesel fuel as                 ameans of reducing exhaust emissions. The addition of (2-ethylhexyl nitrate) was designed to raise fuel cetane number to three stages, 50, 52 and 55 compared to the used conventional diesel fuel whose CN was 48.5. The addition of CN improver results in the decrease brake specific fuel consumption by about 12.55%, and raise brake thermal efficiency to about 9%.Simultaneously, the emission characteristics of four fuels are determined in a diesel engine. At high loads, a little penalty on CO and HC emissions compared to baseline diesel fuel. NOx emissions of the higher CN fuels are decreased 6%, and CO of these fuels is reduced to about 30.7%. Engine noise reduced with increasing CN to about 10.95%. The results indicate the potential of diesel reformation for clean combustion in diesel engines.